Synthesis of novel dihydronaphthothiazine S, S-dioxides by intramolecular sulfonylamidomethylation of 2-naphthylmethanesulfonamides using Amberlyst XN-1010. Issue 52 (30th December 2015) - Sasiambarrena, Leandro D.; Cánepa, Alicia S.; Bravo, Rodolfo D.
Graphical abstract: Abstract: We describe herein an efficient synthetic method for novel dihydronaphthothiazines S, S -dioxides by aromatic intramolecular sulfonylamidomethylation of 2-naphthylmethanesulfonamides with s -trioxane using Amberlyst XN-1010 as acid heterogeneous catalyst. Cyclization of the formed sulfonyliminium ion occurred with high regioselectivity and in excellent yields.